Прагматичні особливості представлення знань у сучасному англомовному лекційному дискурсі - Смаль, Оксана Віталіївна; Smal, O. V. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Виділено та охарактеризовано комунікативно-прагматичні засоби в сучасному англомовному лекційному дискурсі, за допомогою яких здійснюється вплив автора-лектора на студента-читача. Окреслено здатність лекційного дискурсу привертати, утримувати й маніпулювати увагою читача-студента. Визначено мовні одиниці, що логічно поєднують одне речення з іншим, а також одну частину лекційного матеріалу з наступною. Виокремлено особливості вживання різних дискурсивних маркерів на різних етапах лекції. Проаналізовано спосіб представлення знань задля досягнення максимального ефекту сприйняття інформації у письмових фіксаціях лекцій. Здійснено кількісний аналіз частотності застосування засобів привертання уваги студента-читача, згідно з яким найчастотнішими є засоби протиставлення та організації дискурсу, що сприяють виділенню основної та другорядної інформації, уточненню лекційного матеріалу, його успішному поясненню.

The article covers the main features of pragmatic peculiarities of knowledge representation in contemporary English lecture discourse. Communicative and pragmatic means were distinguished and characterized in a contemporary English lecture discourse, with a help of which the influence of the author-lecturer on the student-reader is made. The reference has been made to the lecture discourse ability to attract, retain and manipulate the reader’s attention. Linguistic units that logically combine one sentence with another and also one part of the lecture material with the next one are defined. The use of different features of discourse markers at various stages of the lecture is determined. The way of knowledge representation is analyzed for maximum perception effect of information provided in the written lecture fixations. A quantitative frequency analysis of the use of means of the student-reader’s attention attraction is done, according to which the most frequent are means of opposition and discourse organization that promote the release of primary and secondary information, the clarification of lecture material, its successful explanation.
Pragmatic Peculiarities of Knowledge Representation in Contemporary English Lecture Discourse.
Keywords: комунікативно-прагматичні засоби; лекційний дискурс; дискурсивний маркер; інформація; увага; communicative and pragmatic means; lecture discourse; discourse marker; information; attention